1‐3‐Type Composites Based on Ferroelectrics: Electromechanical Coupling, Figures of Merit, and Piezotechnical Energy‐Harvesting Applications. Issue 5 (23rd March 2018) - Bowen, Christopher R.; Topolov, Vitaly Yu.; Zhang, Yan; Panich, Alexander A.
Abstract: The physical and microgeometric factors that are able to improve the piezoelectric performance, anisotropy, and energy‐harvesting characteristics of modern 1‐3‐type composites based on ferroelectrics are discussed. The composite connectivity patterns of particular interest for this study include 1‐3‐0, 1‐0‐3, and 1‐2‐2. The active components of the studied composites are chosen from conventional perovskite‐type ferroelectric ceramics, lead‐free materials, or domain‐engineered single crystals, all of which exhibit particularly intriguing electromechanical properties. Examples of the large anisotropy of piezoelectric coefficients, electromechanical coupling factors, squared figures of merit, and large hydrostatic parameters of the three‐component 1‐3‐type composites are considered in the context of their piezotechnical applications. The applications of these materials include piezoelectric transducers, sensors, energy‐harvesting, and hydroacoustic devices. Abstract : Think compositive : Physical and microgeometric factors that improve the piezoelectric performance, anisotropy, and energy‐harvesting characteristics of modern 1‐3‐type composites based on ferroelectrics are discussed. Examples of the large anisotropy of piezoelectric coefficients, electromechanical coupling factors, squared figures of merit, and large hydrostatic parameters are considered in the context of their piezotechnical applications. The applications of these materials include piezoelectric transducers, sensors, energy‐harvesting, and hydroacoustic devices.